2022
DOI: 10.3390/microorganisms10122334
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Dormancy: How to Fight a Hidden Danger

Abstract: Both latent and active TB infections are caused by a heterogeneous population of mycobacteria, which includes actively replicating and dormant bacilli in different proportions. Dormancy substantially affects M. tuberculosis drug tolerance and TB clinical management due to a significant decrease in the metabolic activity of bacilli, which leads to the complexity of both the diagnosis and the eradication of bacilli. Most diagnostic approaches to latent infection deal with a subpopulation of active M. tuberculosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 177 publications
0
11
0
Order By: Relevance
“…Interestingly, both the regrowth and resumption of the pathogen in the alveolar macrophages of some patients were achieved without the use of any special resuscitationpromoting factors or other products of Mtb in a long-term ex vivo culture. Meanwhile, many substances were necessary for resuscitation of Mtb in the different in vitro dormancy models with a wide spectrum of stressful conditions in stationary phase [66][67][68][69] and from the sputum of patients with active TB disease [70], while the Mtb transition from a dormant, nonreplicating state to an actively dividing state was estimated by a standard colony-forming assay. We hypothesize that Mtb, as an intravacuolar pathogen in the viable host cells of TB patients [35], are likely to be able to monitor stressful environments, including exposure to anti-TB drugs, through the interaction of the Mtb phagosomes and human endocytic pathways, as we have established previously [35], and to quickly resume the growth in favorable conditions, especially in colonies with cording morphology, for some patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both the regrowth and resumption of the pathogen in the alveolar macrophages of some patients were achieved without the use of any special resuscitationpromoting factors or other products of Mtb in a long-term ex vivo culture. Meanwhile, many substances were necessary for resuscitation of Mtb in the different in vitro dormancy models with a wide spectrum of stressful conditions in stationary phase [66][67][68][69] and from the sputum of patients with active TB disease [70], while the Mtb transition from a dormant, nonreplicating state to an actively dividing state was estimated by a standard colony-forming assay. We hypothesize that Mtb, as an intravacuolar pathogen in the viable host cells of TB patients [35], are likely to be able to monitor stressful environments, including exposure to anti-TB drugs, through the interaction of the Mtb phagosomes and human endocytic pathways, as we have established previously [35], and to quickly resume the growth in favorable conditions, especially in colonies with cording morphology, for some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results strongly suggest that the modulation of the LAM content that was detected in both the pathogenic and non-pathogenic mycobacteria, is a well-coordinated, growth phase-and environmental-signal-regulated process likely affecting the cell wall integrity and unique acid-fast property of mycobacteria. Overall, while in vitro and in vivo animal models remain some of the main sources of knowledge about the mechanisms of Mtb survival under multiple stressful conditions (reviewed in [68,69]), they are unlikely to reflect the actual situation in human TB disease or the true interaction between the pathogen and host cells under the treatment of TB patients. Therefore, future studies of Mtb persistence, dormancy, and resumption as well as the identification of biomarkers characterizing these phenomena and the biological states and growth features of the pathogen in humans are very important.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the presence of DD Mtb cells in the sputum produced by patients with active TB. These cells are not able to form colonies on standard glycerol-based solid media (7H10 agar plates and Löwenstein-Jensen slants) but can grow in liquid media supplemented with mycobacterial culture filtrates (CF) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 61 , 62 ] or other substances, such as cyclic-AMP [ 17 ] and fatty acids [ 63 , 64 ]. The growth stimulatory effect of CF was ascribed to the five resuscitation-promoting factors (Rpfs) of Mtb, which have the ability to resuscitate non-culturable cells [ 12 , 65 ].…”
Section: Differentially Detectable (Dd) Mtb Cellsmentioning
confidence: 99%
“…This process can cause productive cough, enabling pathogen spread to different lung areas [11]. The bacterium may also remain dormant in a non-replicating granuloma state, leading to a latent form of M.tb [12] (Fig. 1).…”
Section: Introduction To Mycobacterium Tuberculosismentioning
confidence: 99%